Advances in therapeutic targeting of immune checkpoints receptors within the CD96-TIGIT axis: clinical implications and future perspectives. (2nd December 2022) - Farhangnia, Pooya; Akbarpour, Mahzad; Yazdanifar, Mahboubeh; Aref, Amir Reza; Delbandi, Ali-Akbar; Rezaei, Nima
ABSTRACT: Introduction: The development of therapeutic antibodies targeting immune checkpoint molecules (ICMs) that induce long-term remissions in cancer patients has revolutionized cancer immunotherapy. However, a major drawback is that relapse after an initial response may be attributed to innate and acquired resistance. Additionally, these treatments are not beneficial to all patients. Therefore, the discovery and targeting of novel ICMs and their combination with other immunotherapeutics are urgently needed. Areas covered: There has been increasing evidence of the CD96-TIGIT axis as ICMs in cancer immunotherapy in the last five years. This review will highlight and discuss the current knowledge about the role of CD96 and TIGIT in hematological and solid tumor immunotherapy in the context of empirical studies and clinical trials, and provide a comprehensive list of ongoing cancer clinical trials on the blockade of these ICMs, as well as the rationale behind combinational therapies with anti-PD-1/PD-L1 agents, chemotherapy drugs, and radiotherapy. Moreover, we share our perspectives on anti-CD96/TIGIT-related combination therapies. Expert opinion: CD96-TIGIT axis regulates anti-tumor immune responses. Thus, the receptors within this axis are the potential candidates for cancer immunotherapy. Combining the inhibition of CD96-TIGIT with anti-PD-1/PD-L1 mAbs and chemotherapy drugs has shown relatively effective results in the context of preclinical studies and tumor models.